Аналіз інформаційних загроз у безпроводових мережах підприємства - Куля, Ю. Е. (ХНУРЕ, 2021)
Analysis of the current situation shows that the main reason for the indecision of the transition to wireless networks is the problem of information security, the level of which for both individual lines and for the system as a whole has not yet been determined. Wireless networks use air and space to transmit and receive information. Ensuring that the confidentiality and integrity of information is properly protected when it is transmitted between workstations and access points is a very important aspect of the security of the system as a whole. Due to the wide availability of wireless devices and their low cost, security breaches occur. The specifics of wireless networks provide that data can be intercepted and changed at any time.
Keywords: інформаційні загрози; безпровідні мережі підприємства